Work in a Sitting Position at an Ergonomic Workstation to Reduce Complaints and Fatigue to Increase Work Productivity - Gempur Santoso (International Journal of Scientific Multidisciplinary Research, 2024)
This article discusses the egonomic position of sitting in a work station chair, because many workers still experience complaints and fatigue when working in a sitting position at a work station. Thus, it is hoped that the sitting position at an ergonomic work station can increase work productivity. This article is written descriptively. Then, all the data that will be processed and discussed is obtained from various opinions or what is called literature study. The analysis used is also descriptive, then concluded. Conclusion: 1) when making chairs and work tables, you must pay attention to the user's anthropometric dimensions. Thus, when working in a sitting position, the legs must be able to lean back (legrests must be provided on chairs and tables), the vertebrae, especially the lumbar spine, must be able to lean against the back of the chair, the angle of the knees can be adjusted at the elbows, a strong chair does not collapse easily for chairs with wheels. chair with five-wheeled legs, when sitting on the knees it must fit under the chair freely, on the work table there must be an area used for work (usual area) and an area sometimes used (occasional area) all of this is made according to the size of the user's hand reach and can also be increased in size table for the outer reach zone area. Then, the work station environment is adjusted to the threshold values, including lighting, climate (temperature, wind speed, humidity), noise, vibration and ultraviolet exposure. 2) that ergonomic work desk chairs and work stations will reduce musculoskeletal complaints and worker fatigue which in the end can increase work productivity